Monthly Runoff Prediction Based on STL-CEEMDAN-LSTM Model - WANG Hai; SHEN Yanqing; QI Shansheng; PAN Hongzhong; HUO Jianzhen; WANG Zhance (Renmin Zhujiang)
According to the nonlinear and non-stationary characteristics of monthly runoff sequences, the quadratic decomposition method was combined with machine learning to construct a model for predicting monthly runoff. This model uses a seasonal trend decomposition procedure based on loess (STL) to decompose the measured monthly runoff sequence into trend terms, seasonal terms, and residual terms with different frequencies. The complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) algorithm was then applied to decompose the residual terms to obtain intrinsic mode functions (IMFs) of different frequency components. Finally, the trend term, seasonal term, and each modal component IMF were used as inputs for the long short term memory network (LSTM) for training and prediction. The model was validated with measured monthly runoff data from Tangnaihai hydrological station in the upper reaches of the Yellow River and was compared and analyzed with other models. The results show that the STL-CEEMDAN-LSTM prediction model has a good simulation effect. The Nash Sutcliffe efficiency (NSE), root mean square error (RMSE), and R2 in the model prediction period are 0.813, 239.02, and 0.810, respectively, with the prediction accuracy better than the single model and the primary decomposition model. The secondary decomposition of STL-CEEMDAN can effectively improve the prediction accuracy of the model.